Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) Terhadap Hasil Belajar Siswa Pada Subtema 3 Lingkungan Dan Manfaatnya Di Kelas V UPTD SD Negeri 122355 Pematang Siantar - Vinny Apriliana Purba (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research was motivated by the low learning outcomes of class V UPTD students at SD Negeri 122355 Pematang Siantar. Contextual teaching learning (CTL) learning model on student learning outcomes in subtheme 3 Environment and its Benefits. The aim of this research is to determine whether or not there is an influence of the contextual teaching learning (CTL) learning model on student learning outcomes in subtheme 3 environment and its benefits. The approach to this research is a quantitative approach. Hypothesis test results using SPSS 21 analysis. It is known that the tcount result is 30.159. The ttable value in the statistical table with a significance of 0.05 with df n-2 is 1.68709. Because tcount (11.256) > (1.68709), the Contextual Teaching Learning (CTL) learning model influences student learning outcomes. In conclusion, regarding student learning outcomes in subtheme 3 Environment and its Benefits